CROSSING BRIDGES: CROSS-CULTURAL ADAPTATION AND SOCIAL INTERACTION OF INTERNATIONAL STUDENTS IN MALAYSIA - Pragash MuthuRajan; Sultana M Alam, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The globalization of education has led to a rise in international student mobility, with Malaysia becoming a key destination. However, research on the cross-cultural adaptation of international students in Malaysia remains limited. This study examines the adaptation experiences of 958 international students across 20 universities, focusing on their perceptions of interactions and relationships with Malaysians. The results indicate that most students report positive adaptation outcomes, including emotional closeness to Malaysians, a sense of being understood, and active participation in academic and social activities. However, some students feel disconnected, citing barriers like language and cultural differences. The study recommends strengthening orientation programs, peer mentoring, and cultural sensitivity training to improve integration, and encourages local students to foster inclusive environments. The findings have practical implications for enhancing the cross-cultural experience and well-being of international students.